Immunomodulatory effect of metabolites from digested and fermented fractions from irradiated pineapple (Annanas comosus L.) snack-bars. (30th March 2022) - Del Juncal-Guzmán, Diana; Antunes-Ricardo, Marilena; Sánchez-Burgos, Jorge A.; Sáyago-Ayerdi, Sonia G.; Gutiérrez-Uribe, Janet A.
Graphical abstract: Highlights: Irradiated pineapple snack-bars (IPB) and non-irradiated (NIPB) showed 40 free phenolics. Hydroxycinnamic acids in NIPB 47.9 and IPB 44.2% were the most abundant group. 28 bound phenolics being tentative identified Feruloyl Aldarate III as most abundant. Digested and fermented fractions of NIPB and IPB exerted an immunomodulatory effect. PC in intestinal and fermented fractions inhibited IL-6 production. Abstract: Phenolic compounds (PC), can modulate the immune response. UV-C irradiation, commonly used as a minimal processing method in fresh-foods to reduce the microbial load, increase shelf-life, provide a minimal processing and facilitate the release of PC. This study aimed to evaluate the effect of intestinal (IF) and fermented (FF) fractions of non-irradiated (NIPB) and irradiated (IPB) pineapple snack-bars on the production of nitric oxide (NO), interleukin 6 (IL-6), cyclooxygenase 2 (COX-2), and tumor necrosis factor-alpha (TNF-α) in mice macrophages. IF of NIPB and IPB exerted an immunomodulatory effect by promoting the production of NO (26 pg/mL) in both treatments, COX-2 (438 and 399 pg/mL), and TNF-α (778 and 802 pg/mL) for NIPB and IPB respectively. The TNF-α increased in IF of NIPB and IPB approximately 371 %, and in FF, only increased 132 %. The NO production was not different between IF and FF. COX-2 production was higher in FF.